CLIL Projects for Critical Thinking and Digital Citizenship in Moroccan Classrooms - Bendraou, Rachid; ALAOUI HICHAMI, Taoufik (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
This study examines the effect of Content and Language Integrated Learning (CLIL) project-based learning, incorporating Moroccan culture and digital citizenship, on the critical thinking, cultural consciousness, and local identity of first-year middle school students in Morocco. The study employs a quasi-experimental design, involving an experimental group (n = 28) instructed using the CLIL strategy and a control group (n = 28) receiving traditional instruction. To evaluate progress in their critical thinking abilities and knowledge of Moroccan cultural traits, both groups were administered pre- and post-tests. The data was analysed using paired t-tests, which demonstrated a substantial increase in the post-test scores of the experimental group compared to the control group. These results indicate that integrating digital citizenship and local culture into CLIL can improve the critical thinking skills and cultural awareness of students. The significance of culturally applicable content and pedagogical approaches in the development of intercultural competence and awareness is underscored by the study. The results are limited by the small sample size and brief duration, indicating the necessity of additional research with larger, more diverse samples and extended time frames to verify them and investigate CLIL's effects in a variety of educational contexts.